Executive Function Assessment in Patients With Idiopathic Generalized Epilepsy: Applyingthe Frontal Assessment Battery - Asadollahi, Marjan; Roozbeh, Mahrooz; Edalatkhah, Amin; Roozbeh, Mehrdad; Mirzaei, Nasim; Rostami, Mohammad; Simani, Leila (International Clinical Neuroscience Journal, 2021)
Background: Executive dysfunction is seen in idiopathic generalized epilepsy (IGE). The Frontal Assessment Battery (FAB) is a short neuropsychological instrument designed in clinical settings to evaluate frontal lobe activity. We aimed to assess the clinical use of FAB in patients with IGE for to detect executive impairment. Method: In this study, 30 patients with IGE and 30 age- and sex-matched healthy controls were included. The presence and severity of executive dysfunction was investigated with FAB. Cognitive flexibility, decision making, working memory, and general intelligence level were examined using Wisconsin Card Sorting Task (WCST), Iowa Gambling Task (IGT), N-back, and Wechsler Adult Intelligence Scale, respectively. In patients with IGE, FAB results were related to their neuropsychological task performance. Results: The FAB score in patients with IGE was significantly lower compared to healthy participants. In motor programming tasks, patients with IGE performed substantially worse. However, no correlation was found between FAB and neuropsychological task and clinical characteristics. Conclusion: Executive dysfunction was present in patients with IGE and FAB may be used in these patients as an effective tool for evaluating frontal lobe function.